Automatic slice growing method based 3D reconstruction of liver with its vessels - Alom, Md. Zahangir; Mostakim, Moin; Biswas, Rubel; Chakrabarty, Amitabha (© 2014 Institute of Electrical and Electronics Engineers Inc., 2016)
This conference paper was presented in 16th International Conference on Computer and Information Technology, ICCIT 2013; Khulna; Bangladesh; 8 March 2014 through 10 March 2014 [© 2014 IEEE] The conference paper's definite version is available at: http://dx.doi.org/10.1109/ICCITechn.2014.6997361